The Last Lion : Winston Spencer Churchill : Alone 1932-1940 - Manchester, William (Boston Little, Brown and Company, 1988)
The noted biographer-historian continues his life of Winston Churchill, focusing here on the years of Churchill's political exile and his increasingly forceful opposition to Hitler's Germany
Include Note and Index
Keywords: Great Britain -- Churchill, Winston, 1874-1965 -- Diplomatic relations -- Politics and government